Revolutionizing the runway: how technological and marketing innovation fuse market sensing on marketing performance in fashion industry - Jeskhael Este Sutanto; Eric Harianto; Denpharanto Agung Krisprimandoyo (Cogent Business & Management, 2024)
This research attempts to explore the uses of market sensing and marketing performance through technological innovation and marketing innovation of local SMEs that offer their branded products in the fashion industry. While many previous studies discuss technological and marketing innovation in well-established fashion industries, this study attempts to relate market sensing and marketing performance from the less-established home fashion industry. Methodology, the sampling method uses purposive sampling with 142 respondents. The data processing used SmartPLS, evaluating the reflective measurement model and the structural model. Findings, the analysis of the structural equations shows that all variables of direct effect have a positive and significant effect. The final value, this paper will provide a direct contribution to increasing the amount of literature and to practitioners who have contributed knowledge related to market sensing variables on marketing performance, which are the variables of technological innovation and marketing innovation.
Keywords: 650; Market Sensing; Marketing Performance; Technological Innovation; Marketing Innovation; Fashion Industry